Identification and characterization of lbpA, an indigoidine biosynthetic gene in the γ-butyrolactone signaling system of Streptomyces lavendulae FRI-5 - Ivy Grace Umadhay Pait (2018)
© 2017 The Society for Biotechnology, Japan Streptomyces lavendulae FRI-5 produces the blue pigment indigoidine and other secondary metabolites (D-cycloserine and nucleoside antibiotics). The production of these useful compounds is controlled by a signaling cascade mediated by the γ-butyrolactone autoregulator IM-2. Previously we revealed that the far regulatory island includes the IM-2 receptor, the IM-2 biosynthetic enzyme, and several transcriptional regulators, and that it contributes to the regulation of indigoidine production in response to the signaling molecule. Here, we found that the vicinity of the far regulatory island includes the putative gene cluster for the biosynthesis of indigoidine and unidentified compounds, and demonstrated that the expression of the gene cluster is under the control of the IM-2 regulatory system. Heterologous expression of lbpA, encoding a plausible nonribosomal peptide synthetase, in the versatile model host Streptomyces avermitilis SUKA22 led to indigoidine production, which was enhanced dramatically by feeding of the indigoidine precursor L-glutamine. These results confirmed that LbpA is an indigoidine biosynthetic enzyme in the IM-2 signaling cascade.